Narrativa (auto) biográfica e a dimensão pictórica da “colcha de retalhos”: a experiência estética como autonomia e emancipação dos sujeitos no curso de pedagogia - Silva, Alexandre Ferreira da (2021)
The present study aims to understand the meaning of aesthetic experience in its pictorial dimension in the formative path of teachers in the Pedagogy Course; It aims to understand the images of the flaps built by the participants of the “Colcha de Retalhos” formative device, envisioning the construction of autonomy and emancipation. The development of this research is permeated by the concepts related to (auto) biographical narratives, through Josso (2004; 2007), Delory- Momberger (2012; 2014) Passeggi (2010; 2011; 2016), for the foundation of the “Bedspread Patchwork”, Berkenbrock-Rosito (2009). Concepts about Aesthetic Education are also presented in the perspective of Schiller (2002), with the contributions of Perissé (2009), in addition to the conceptions of autonomy and emancipation treated mainly by Freire (1995; 1996) and Adorno (2002; 2008; 2011), with its cultural industry bias and the semi-training process. Visual Culture is presented by studies mainly by Joly (2007) and Martins (2006). The semiotics approach brought by Peirce (2005) and Santaella and Nöth (1998) contribute to the analysis of pictorial narratives, whose central element is addressed by Moro (2016) and Lopes (2015). The adopted methodology is the documentary analysis of primary source: the scraps produced by the students, treated as historical documents that allow the verification of significant aspects for the expansion of the understanding about the formation of teachers in the Pedagogy course. The data were understood under the hermeneutic approach from the perspective of Gadamer (2000). The formative device “Patchwork Quilt” and the data collected from its application allowed us to immerse ourselves both in the possible aesthetic experiences lived by the students, as well can also illustrate part of the students' aesthetic-formative path in the Pedagogy Course. The data show the possibility of understanding human formation from the (auto) biographical narrative in the pictorial dimension, revealing a process of reflection. Flaps, like images, constitute a possibility for the construction and production of knowledge in the development of the subjects' autonomy and emancipation.